A checkpoint cliffhanger at the dawn of placental mammals - Dustin, ML; Zenclussen, AC (American Society for Biochemistry and Molecular Biology, 2020)
The PD-1 ligands PD-L1 and PD-L2 are commonly expressed on the surface of cells, where they regulate immune system activation. However, the specific role played by each ligand has been unclear. Using site-directed mutagenesis, surface plasmon resonance, and crystallography, Philips et al. explore the distinct features of PD-L2 and identify a specific evolutionary event linked to its appearance. This work provides a deeper understanding of how the immune system adapted to mammalian placental gestation and could be an important consideration in the development of new immune checkpoint therapies.